Perils of Internet fraud: an empirical investigation of deception and trust with experienced Internet consumers - Grazioli, S.; Jarvenpaa, S.L. (IEEE transactions on systems, man and cybernetics. Part A, Systems and humans, 2000)
This study examines consumer evaluations of a real commercial web site and a fraudulent site that imitates it. The forged site contains malicious manipulations designed to increase trust in the site, decrease perceived risk, and ultimately increase the likelihood that visitors would buy from it. Besides measuring the consumer's willingness to buy from the site, this study recorded the actual ordering of a laptop. Results show that most subjects failed to detect the fraud manipulations, albeit a few succeeded. The fraud has the effect of increasing the consumers' reliance in assurance mechanisms and trust mechanisms, which in turn decrease perceived risk and increase trust in the store. The study confirms hypothesized relationships between purchase behavior, willingness to buy, attitudes toward the store, risk, and trust that are consistent with other trust models found in the literature. Overall, the study sheds light on consumers' vulnerability to attack by hackers posing as a legitimate site.